Assessment of pregnant women’s knowledge and practices concerning prenatal care who attend primary health care centers in Baghdad City - Shalash, Ishraq; Mohammed, Fatin (Iraqi National Journal of Nursing Specialties, 2012)
Objective: To assess knowledge of pregnant women concerning prenatal care who attend primary health carecenter in Baghdad city.Methodology: A descriptive analytic study carried on (100) pregnant women who attend primary health carecenters in Baghdad city (50) of them from Al- Sheik Omer primary health care center \Resafa sector .and 50 fromBelat Al-Shuhadaa/ Al Karch sector, during the period from April to November 2011. The data were collectedthrough interview and use questionnaire format. Validity and Reliability of the questionnaire were determinedthrough panel of experts and pilot study, data were analysed through the application of descriptive statisticalanalysis and inferential statistical analysis.Results: The results revealed that (28%) of pregnant women their ages ranged between 15-19 years, (48%) werenot read and write, (54%) from low socioeconomic status. (61%) had 1-2 gravida, (48%) had 1-2 para, 26% had 1-2abortion and 78%attended primary health care center 1-2 visits only. The result indicates that there is no significantrelationship between sociodemographic characteristic and knowledge of pregnant women concerning prenatalcare, while there is significant relationship between number of prenatal care visits and knowledge of the pregnantwomen.Recommendations: The study recommended an emphasis on health education for mothers' awareness of theimportance of regular visits to primary health care center during pregnancy.